1996
DOI: 10.1097/00007691-199606000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Pharmacokinetics of Methadone in Chronic Pain Patients

Abstract: Ten patients with chronic pain were randomized to an open, balanced, crossover study. Each patients received two different preparations of racemic methadone, i.e., tablets and intravenous infusion. The pharmacokinetic parameters of the R- and S-enantiomers of the racemate are reported. The analgesically active R-methadone has a significantly longer mean elimination half-life than the optical antipode S-methadone (t1/2 = 37.5 and 28.6 h, respectively). The mean total volume of distribution is 496.6 L for R-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
2
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 21 publications
8
70
2
2
Order By: Relevance
“…É um agonista dos receptores opióides Mµ, Delta e Kappa. A metadona também é um antagonista do receptor NMDA e parece bloquear a recaptação de serotonina e noradrenalina 22,23,26,27 . A absorção após administração oral de metadona em solução ou comprimidos é rápida e quase completa.…”
Section: Conclusion -Although the Growing Knowledge On The Use Of Opunclassified
See 3 more Smart Citations
“…É um agonista dos receptores opióides Mµ, Delta e Kappa. A metadona também é um antagonista do receptor NMDA e parece bloquear a recaptação de serotonina e noradrenalina 22,23,26,27 . A absorção após administração oral de metadona em solução ou comprimidos é rápida e quase completa.…”
Section: Conclusion -Although the Growing Knowledge On The Use Of Opunclassified
“…Metadona não é removida pela hemodiálise. Também está presente no leite materno em concentrações que teoricamente não impedem a amamentação, porém cruza a barreira placentária em concentração que pode causar síndrome de abstinência no recém-nascido de mães que usam metadona 22,23,25,27,28,[31][32][33] . A metadona produz menos náusea, constipação e sedação do que a morfina.…”
Section: Conclusion -Although the Growing Knowledge On The Use Of Opunclassified
See 2 more Smart Citations
“…Studies in chronic pain and opioid replacement patients have shown different pharmacokinetic characteristics of the enantiomers. However, the bioavailabilities and AUCs of the latter did not differ in any of these studies [28,29]. Thus, our data on racemic bioavailability probably reflects those of the respective enantiomers.…”
Section: Iv-rectal (᭹)mentioning
confidence: 57%